Efeitos renais e alterações morfológicas causadas pelo peptídeo natriurético sintético do veneno Crotalus durissus cascavella - Silveira, João Alison de Moraes (2015)
Natriuretic Peptides (NPs) have significant interest in regulating the cardiovascular, renal and endocrine homeostasis, and have been described in the venom of venomous snakes. Crotalus durissus cascavella, a characteristic terrestrial snake of caatinga biome of northeastern Brazil, has in his whole venom an NP (NPCdc), of which are reported vascular and renal effects. The aim of this study was to synthesize NPCdc in solid phase and evaluate its renal actions through isolated kidney perfusion and culture of renal tubular cells of MDCK and LLC-MK2 line. Kidneys from male Wistar rats weighing 250-300 g were surgically excised and perfused with modified Krebs-Henseleit solution with 6 g% of previously dialyzed bovine serum albumin. The effects of NPCdc were investigated in four concentrations (0.03 μg/mL, 0.1 μg/mL, 0.3 μg/mL and 1 μg/mL, n=6). MDCK and LLC-MK2 cells were cultured in RPMI 1640 culture medium supplemented with 10% v/v Fetal Bovine Serum and then evaluated in presence of several concentrations of NPCdc at an incubation period of 24 hours. After this period, cell viability assays were performed. Data were statistically compared considering P<0.05. There was increase in perfusion pressure (PP) in 0.03 μg/mL and reduction in 1 μg/mL. Renal vascular resistance (RVR) was increased at 0.03 μg/mL. Urinary flow (UF) increased in 0.03 μg/mL and decreased in 0.1 μg/mL and 1 μg/mL. The glomerular filtration rate (GFR) was reduced at all the concentrations tested. Osmolar clearance (OsmC) was increased in 0.03 μg/mL and reduced in 0.1 μg/mL and 1 μg/mL. Percentage of the total and proximal tubular transport of sodium (%TNa+ and %pTNa+, respectively) and chloride (TCl-% and pTCl-%, respectively) showed reductions at all concentrations tested. Percentage of the total proximal tubular transport and potassium (%TK+ and pTK+%, respectively) were reduced in 0.03 μg/mL and 0.3 μg/mL. The histopathological analysis revealed the presence of significant morphological changes, such as concentration-dependent hydropic degeneration at all concentrations, along with mild to moderate deposition of proteinaceous material in the tubules in concentration 0.03 μg/mL. In the culture of MDCK and LLC-MK2 cells, however, NPCdc was not able to lower cell viability. These results demonstrate that NPCdc modified all parameters assessed in renal perfusion of isolated kidney, and showed cytotoxic alterations in histopathological analysis, however, not presenting it in cultures of renal tubular cells.